Winning the game against fake news? Using games to inoculate adolescents and young adults in Singapore against fake news - Tandoc, Edson C. (2024)
Guided by inoculation theory and studies that examined serious games as a form of intervention to inoculate individuals against fake news, this study tested the impact on college (n = 84) and junior high and secondary school (n = 30) students of a fake news computer game developed in Singapore. The findings were replicated across both samples: Those who played the game subsequently improved in their self-reported scores on perceiving fake news as a threat, skepticism toward information from social media, and being cautious about believing in information they encounter online. We also found that those who played the game scored higher in detecting fake news than those who did not play the game–consistent with the predicted effects of message inoculation.